Sensory Evaluation and Acceptability of Cala-Mango Butchi - Pugong, Gina Mae Uddang (Journal TECHNO, 2024)
Pugong, Gina Mae U. (2024). Sensory Evaluation and Acceptability of Cala-Mango Butchi.          This study presents the importance of snacks in many Filipinos daily food intake. It also states the benefits and uses of mangoes and calabash fruit. This study aims to: produce a food product which can help farmers dispose of their products and create an additional income; make a local food which is healthy and affordable; utilize and maximize the use of mangoes and calabash fruit. This study also focused in assessing the acceptability cala-mango butchi. This study used the quantitative descriptive survey method of research. It is appropriate in this study because it allows for standardized measurement using numerical rating scale and enables statistical analysis. Moreover, the qualitative approach by observing the reactions of the respondents were considered. Gathered data were analyzed and interpret with the use of mean and percentage. Percentage is used to describe the profile of the respondent. Mean is used to determine the acceptability of the butchi in terms of its aroma, appearance, flavor and texture. Results showed that the respondents have different perception about cala-mango butchi but in summary this product is very much accepted by the respondents in terms of appearance, texture, aroma and flavor. This study recommends to future researchers to consider making butchi with other flavors and do a larger scale of sampling. They may also consider adding marketability research.